Analisis Nilai Tambah dan Strategi Pengembangan Produk Mi Mocaf di UMKM Mekarsari Kabupaten Boyolali - Wijaya, Edward Surya; Budiraharjo, Kustopo; Handayani, Migie (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The massive development of the mocaf noodle industry has increased the competitiveness of alternative food products with wheat flour products. This research aims to analyze costs and revenue, product added value, and identify internal and external factors to formulate a strategy for the development of Mie Hend's products in UMKM Mekarsari. The research was conducted in February – March 2025 at UMKM Mekarsari, Boyolali. The location determination is based on the consideration that UMKM Mekarsari are a producer of gluten-free mocaf noodles in Central Java. The research method uses the case study method. Sampling was done using purposive techniques and accidental techniques. Purposive technique to UMKM Mekarsari owners and representatives of the Central Java Provincial Food Security Office. Accidental technique to 20 consumers of Mie Hend's. Data collection through interviews, observations, and documentation. Data analysis is descriptive quantitatively, including cost, revenue, and revenue analysis, Hayami method value-added analysis, and SWOT and QSPM methods for product development strategies. The results were obtained that UMKM Mekarsari incurred an average production cost of IDR 1,181,778/month and an average income of IDR 1,224,472/month throughout 2024. The added value of Mie Hend's products is relatively high, namely IDR 97,700/kg with a ratio of 81.42% for retail packaging and IDR 73,533/kg with a ratio of 81.70% for bulk packaging. Internal and external analysis through IFAS and EFAS matrices resulted in that Mie Hend's products are in quadrant I of the SWOT diagram which is ideal for implementing SO or aggressive strategies. The resulting alternative strategies are 1) regularly refreshing products to maintain product quality and consumer trust, 2) penetrating digital markets and partnerships, and 3) submitting cooperation with health institutions, especially related to autism. Prioritize strategy by penetrating the digital market and partnerships.